Incidence of Patients with Lower Extremity Injuries Presenting to US Emergency Departments by Anatomic Region, Disease Category, and Age - Lambers, Kaj (Springer-Verlag, 2011)
BACKGROUND: The incidence of patients with lower extremity injuries presenting to emergency departments in the United States with respect to specific anatomic regions and disease categories is unknown. Such information might be used for injury prevention, resource allocation, and training priorities. QUESTIONS/PURPOSES: We determined the anatomic regions, disease categories, and circumstances that account for the highest incidence of leg problems among patients presenting to emergency departments in the United States. METHODS: We used the National Electronic Injury Surveillance System (NEISS) to obtain a probability sample of all lower extremity injuries treated at emergency departments during 2009. A total of 119,815 patients who presented to emergency departments with lower extremity injuries in 2009 were entered in the NEISS database. Patient and injury characteristics were analyzed. Incidence rates for various regions, disease categories, injuries, and age groups were calculated using US census data. RESULTS: We identified 112 unique combinations of disease categories and anatomic regions. Strains and sprains accounted for 36% of all lower extremity injuries. The injury with the greatest incidence was an ankle sprain (206 per 100,000; 95% confidence interval, 181–230). Younger patients were more likely to have ankle sprains, foot contusions/abrasions, and foot strains/sprains. Older patients were more likely to have lower trunk fractures and lower trunk contusions/abrasions. The most common incidence for injury was at home (45%). CONCLUSIONS: Given relatively low-acuity leg problems such as strains and sprains account for a substantial number of emergency department visits pertaining to leg problems, use of telephone triage, scheduled same or next-day urgent care appointments, and other alternatives to the traditional emergency room might result in better use of emergency healthcare resources.